Pengembangan Usaha Kantin Pelangi dalam Upaya Mempertahankan Sustanaibility - Kara, Krispina; Gobang, Emerentiana Ema; Dengu, Putrisia; Natalia Bhoko Oematan, Neldis (INCOME: Indonesian Journal of Community Service and Engagement, 2023)
This community service aims to implement a computer-based bookkeeping system and apply Microsoft Excel properly and correctly in the management of MSMEs in the Pelangi canteen business as well as providing a way to use labels on packaging and use banana leaves as food bases or rice wrappers that are more natural and hygienic and reduce costs. .The method used in this PkM is Skills Training in the form of training and implementing the Excel Application System properly and correctly. The results obtained from this activity are Training on the Implementation of Excel-Based Financial Recording which has provided understanding to MSME managers at the Pelangi Canteen.